Effect of Phenol Derivatives in the Oral Mucosa of University Laboratory Technicians - Ana Paula Nogueira Ferri; Bruna Gomide; Fellipe Augusto Tocchini de Figueiredo; Celina Faig Lima Carta; Ivan Balducci; Janete Dias Almeida (Brazilian Archives of Biology and Technology, 2023)
Abstract The objective of the present work was to quantify the effect of phenolic derivatives on in the oral mucosa of university laboratory technicians. Twenty (20) university laboratory technicians exposed to agents and 11 non-smokers without occupational exposure to phenolic derivatives for more than 10 years underwent anamnesis and extra and intra-oral clinical examination. Exfoliative cytology of the right buccal mucosa was performed. The frequency of micronuclei formation (MN) was analyzed in 1200 cells by standard microscopy. Mann-Whitney and Kruskal-Wallis test were used. The difference between the groups evaluated was observed in the frequency of more than 01 MN/cell (p=0.0397), being more present in the exposed group. The use of personal protective equipment contributed to a decrease in the frequency of 01 MN/cell (p=0.0272) for the exposed group. Genotoxic effects may be reduced by the use of PPE and/or exhaust laminar flow hood. Five years of exposure could adapt the nucleus cells to the genotoxic aggressor demonstrating that the oral mucosa could be a marker to long-term genotoxic exposure.